Pengembangan Strategi Bisnis Kreatif Trikarasu Design dengan Business Model Canvas di Era Digital - Bagus Hardika; Mahesa Dzikri Kurniawan; Cindy Valencia; Wien Kuntari (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
In the digital era, competition in the graphic design industry is increasingly competitive, requiring businesses to innovate and adapt with effective strategies. This study aims to develop business strategies using the Business Model Canvas (BMC) for Trikarasu Design, a start-up in the graphic design field. Employing a qualitative descriptive approach and literature study method, the research maps the nine BMC elements to analyze opportunities and challenges faced. The findings reveal that BMC aids Trikarasu Design in identifying product value propositions, customer segments, and relevant distribution channels. Digital promotion strategies through social media platforms like Instagram and TikTok are proven effective in enhancing visibility and fostering personal relationships with customers. This study provides practical contributions in the form of BMC-based strategies that support the sustainability and growth of Trikarasu Design in the dynamic graphic design market.